The Role of Principal Leadership in Improving Teacher Motivation at SMP Negeri 3 Kertek - Gun Satmiyati; Didi Supriadi; Rejokirono Rejokirono (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to examine the role of principal leadership in improving teacher motivation at SMP Negeri 3 Kertek. The research employed a qualitative descriptive approach involving the principal, teachers, and relevant school stakeholders as participants. Data were collected through interviews, observations, and document analysis and were analyzed using the interactive model of data condensation, data display, and conclusion drawing. The findings reveal that the principal plays a significant role in enhancing teacher motivation through effective communication, instructional supervision, professional development support, recognition of teacher achievements, collaborative school culture, and positive interpersonal relationships. These leadership practices contribute to increased teacher commitment, self-efficacy, job satisfaction, and willingness to implement innovative teaching strategies. Furthermore, improved teacher motivation positively influences instructional quality and overall school performance. The study concludes that transformational and supportive principal leadership is a key factor in fostering teacher motivation and promoting sustainable educational improvement at SMP Negeri 3 Kertek.